Multidisciplinary approach to oral rehabilitation with dental implants after gunshot injury: A clinical report - Nicoli, Lelis Gustavo [UNESP]; Pigossi, Suzane Cristina [UNESP]; Souza Bezerra Araujo, Raphael Ferreira de [UNESP]; Marcantonio, Claudio; Marcantonio, Elcio; Marcantonio, Elcio [UNESP] (Elsevier B.V., 2018)
This clinical report describes a multidisciplinary approach to treat a patient with edentulism and a severe anatomic defect in the mandible caused by a gunshot injury by using an implant-fixed complete dental prosthesis. An immediate loading interim implant-fixed complete dental prosthesis in the mandible associated with a maxillary removable complete denture prosthesis was initially provided to restore the intermaxillary relation. Nasal floor elevation and maxillary sinus augmentation were subsequently performed to increase the maxillary bone volume. Definitive implant-fixed complete dental prostheses were placed in both arches in order to rehabilitate this initially compromised anatomic condition, which ensured patient satisfaction and improvement in masticatory function and esthetics.